QUALITATIVE INSIGHTS FROM TYPE 2 DIABETES PATIENTS AND THE NEED FOR ESTABLISHMENT OF NURSE LED DIABETES CLINICS - Flosy R.Menezes; Dr P.V Rataboli; Dr Leena.K.C (The Bioscan, 2024)
Diabetes is a complex progressive disease, and its treatment requires effective selfmanagement strategies unique to each individual. The aim of the study was to explore the issues and challenges of patients living with type 2 diabetes. A Mixed method research approach was adopted to conduct the study in a tertiary care hospital. Convenient and voluntary participants were selected for the interview. The content was analyzed using Colaizzi’s method of data analysis. Content analysis focused on five main themes. The transcribed data was divided into sub themes. Common issues and challenges faced by type 2 diabetes patients were identified. The identified issues of the individuals need to be channelized in effective patient education system and community nurse led clinics have to/ MUST be established to address the common problems faced by type 2 diabetes patients and reduce the hospital burden.